NORŪZ:: TREADING TIME, NATURE, FAITH AND CULTURE - Amir H. Zekrgoo (Sekolah Tinggi Agama Islam Sadra, 2015)
Norūz, is among the oldest celebrations in history that is still alive and observed by various peoples that historically share Persian culture. This research presents a multifaceted approach to the subject: historical, religious, symbolic and scientific., and is aimed at tracing Norūz in the history, its significance in the setting of an accurate solar calendar, its evolvement in various religious traditions and, eventually, the process of its Islamization. It also provides an analytical account of the “Haft-sīn Spread” – a setting of seven items that are closely associated with the celebration of Norūz – and their symbolic significance.